KILAS BALIK LAJU PERTUMBUHAN EKONOMI DALAM RANGKA PENGUATAN FONDASI EKONOMI PROVINSI KALIMANTAN TIMUR 2011-2013 - Siti Amalia (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2015)
Last three years (2011-2013), macroeconomic conditions in East Kalimantan was encouraging, which is characterized by a relatively GDP that can contribute significantly to the national economy. However, macroeconomic conditions have not been too encouraging East Kalimantan, which is characterized by poverty and unemployment is still relatively large. Although quite high HDI East Kalimantan, but still had not moved from the top five nationally. Slowing economic growth impact on employment conditions, that although the numbers are increasing, but the rate of diminishing productivity. The level of labor productivity decreases make progress reducing poverty also declined. All of these conditions allegedly caused by the direction of development in East Kalimantan are still relying on the extractive sector, making it less able to strengthen the foundation of the economy as a whole. Productive economic sector in East Kalimantan has great potential, given the tendency of this sector has rapidly than other sectors. Thereby strengthening the productive sector of the economy is believed to strengthen the economic foundation of East Kalimantan after the stronger awareness that reliance on extractive sector will only weaken the economic foundations of East Kalimantan as a whole.